2020
DOI: 10.31234/osf.io/xf7ar
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Responsible Product Design to Mitigate Excessive Gambling: A Scoping Review

Abstract: Researchers and gambling operators have developed game-based responsible gambling tools and interventions that are intended to mitigate risks for gambling-related harm. We conducted a scoping review of this literature, with a focus on replicability and transparency. We charted 86 studies on characteristics such as study design and sample size. No tools or interventions had unambiguous evidence of efficacy, but some show promise. Pre-registration of research hypotheses, methods, and analytic plans was absent un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
2
0
0
Order By: Relevance
“…For example, Klein et al (2018) examined 28 classic and contemporary social psychology effects and found that only 54% of the effects replicated. Recently, a z-curve analysis indicated evidence of publication bias and an Expected Replication Rate ranging from 0.61 to 0.79 in the gambling product safety literature (McAuliffe et al, 2020). 4 We note that this range is in line with observations from a number of other social sciences.…”
Section: Implications For Gambling Studies Researchsupporting
confidence: 83%
“…For example, Klein et al (2018) examined 28 classic and contemporary social psychology effects and found that only 54% of the effects replicated. Recently, a z-curve analysis indicated evidence of publication bias and an Expected Replication Rate ranging from 0.61 to 0.79 in the gambling product safety literature (McAuliffe et al, 2020). 4 We note that this range is in line with observations from a number of other social sciences.…”
Section: Implications For Gambling Studies Researchsupporting
confidence: 83%
“…For example, Klein et al (2018) examined 28 classic and contemporary social psychology effects and found that only 54% of the effects replicated. Recently, a z-curve analysis (Brunner & Schimmack, 2019) indicated evidence of publication bias and an Expected Replication Rate ranging from 0.61 to 0.79 in the gambling product safety literature (McAuliffe, Louderback, Edson, LaRaja, & LaPlante, 2020). 4 We note that this range is in line with observations from a number of other social sciences.…”
Section: Implications For Gambling Studies Researchsupporting
confidence: 81%